Inovasi Produk Lokal melalui Transformasi Bahan Pangan Desa Menjadi Produk Bernilai Tinggi di Desa Ngrapah Kecamatan Banyubiru - Rinti Dwijayantie; Raden Roro Diana Atika Ghozali; Rifki Adhi Prasetyo (Yayasan Sumber Daya Manusia Cerdas, 2025)
Community service program was conducted in Ngrapah Village, Banyubiru District, Semarang Regency, with the aim of empowering housewives through training on processing local food ingredients into high-value products. The village’s abundant natural resources, particularly freshwater fish from Lake Rawa Pening, have not been fully utilized to improve household economic welfare. Therefore, a team from the Department of Business and Finance, Vocational School, Diponegoro University, initiated a program to train local women in producing and packaging pempek (traditional Indonesian fish cakes) as a form of downstream processing of local food potential. The program was implemented through a structured approach consisting of needs assessment, technical and managerial training, as well as mentoring in production and marketing. The results indicated a significant improvement in participants’ knowledge and skills, with average scores increasing from 1.9–2.7 before training to 3.8–4.5 afterward. The highest improvements were observed in technical skills for making pempek (from 2.1 to 4.5) and self-confidence to start a business (from 2.5 to 4.4). In addition, at least five participants successfully began independent small-scale production after completing the program. This activity also produced a Standard Operating Procedure (SOP) for pempek production and packaging, which is expected to become the foundation of a collective enterprise to strengthen the village’s economic independence. The program aligns with poverty alleviation efforts and the promotion of food security through community empowerment.